CIA's Eye on South Asia - Dhar, Anuj (New Delhi Manas Publications, 2009)
Insight into the working of Central Intelligence Agency through various reports presented on South Asia from 1951 to 2001.
Include Index.
Keywords: South Asia -- United States. Central Intelligence Agency